2015
DOI: 10.1038/ncomms7393
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial function and lifespan of mice with controlled ubiquinone biosynthesis

Abstract: Ubiquinone (UQ) is implicated in mitochondrial electron transport, superoxide generation and as a membrane antioxidant. Here we present a mouse model in which UQ biosynthesis can be interrupted and partially restored at will. Global loss of UQ leads to gradual loss of mitochondrial function, gradual development of disease phenotypes and shortened lifespan. However, we find that UQ does not act as antioxidant in vivo and that its requirement for electron transport is much lower than anticipated, even in vital m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(136 citation statements)
references
References 70 publications
8
123
1
2
Order By: Relevance
“…A recent intriguing paper supports this hypothesis. Siegfried Hekimi's laboratory has shown that controlled disruption of Coenzyme Q (CoQ) biosynthesis, through knock-out of the Mclk1 gene, severely affects mitochondrial function and dramatically reduces lifespan [38]. Interestingly, restoration of CoQ levels through administration of 2,4-dihydroxybenzoic acid (an analogue of 4-hydroxybenzoic acid, the natural precursor of CoQ) that is only able to partially rescue the mitochondrial phenotype completely rescued the shortened lifespan of Mclk1 mutant mice.…”
Section: Ros Are Not All the Samementioning
confidence: 97%
“…A recent intriguing paper supports this hypothesis. Siegfried Hekimi's laboratory has shown that controlled disruption of Coenzyme Q (CoQ) biosynthesis, through knock-out of the Mclk1 gene, severely affects mitochondrial function and dramatically reduces lifespan [38]. Interestingly, restoration of CoQ levels through administration of 2,4-dihydroxybenzoic acid (an analogue of 4-hydroxybenzoic acid, the natural precursor of CoQ) that is only able to partially rescue the mitochondrial phenotype completely rescued the shortened lifespan of Mclk1 mutant mice.…”
Section: Ros Are Not All the Samementioning
confidence: 97%
“…Likewise, mice with a homozygous deletion of an ETC complex I subunit (Ndufs4 knockout mice) also show reduced longevity. Both of these mutant mouse models are very short‐lived and have severe respiratory and metabolic phenotypes (Kruse et al., 2008; Wang, Oxer & Hekimi, 2015). One explanation for the seemingly contradictory effects of ETC mutation and longevity is a threshold effect in which compromised mitochondrial function alters cellular function only once a critical deficiency in ATP production in reached.…”
Section: Discussionmentioning
confidence: 99%
“…The CoQ10 is 2, 3-dimethoxy-5-methyl-6-decaprenyl-1, 4-benzoquinone (Wang et al, 2015). It contains 10 isoprene units the predominant from in both mammals and birds, whereas CoQ9 (nine isoprene units) is predominant in rodents .…”
Section: Chemistry Of Coenzyme Q10mentioning
confidence: 99%
“…The CoQ10 is similar to vitamin K in its chemical structure but it is not considered a vitamin because it is synthesized in the body (Bhagavan and Chopra, 2006;Wang et al, 2015). All the fat soluble vitamins (A, D, E and K) possess isoprene units in their structures.…”
Section: Introductionmentioning
confidence: 99%